Efficacy of argon‐helium cryoablation and its effects on immune function of patients with neck malignant tumours. (15th October 2020) - Zheng, Zheng; Zhao, Yingchun; An, Yonghui; Li, Na; Bo, Changwen; Ma, Wenhua; Guo, Ying; Zou, Changpeng; Tian, Bo; Zhang, Sujing
Abstract: Objectives: Our study aimed to investigate the clinical efficacy of argon‐helium cryoablation and its effects on the immune function of patients with neck malignant tumours. Design: Retrospective study. Setting: Single‐institution academic tertiary care centre. Methods: Totally, 180 patients harbouring head and neck malignant tumours were divided into the argon‐helium cryoablation group (n = 150) and the radiotherapy group (n = 50). The efficacy of the two groups was compared, and the immune function was observed. Results: The short‐term clinical effect of the argon‐helium cryoablation group was significantly higher than that of the radiotherapy group ( P < .05). After treatment, the CD3+, CD4+, CD8+ and CD4+/CD8+ of the argon‐helium cryoablation group were significantly better than those of the radiotherapy group ( P < .001). The results of TNF‐α, IL‐1 β and CRP in the argon‐helium cryoablation group were significantly better than that in the radiotherapy group ( P < .001). Conclusion: Argon‐helium cryoablation could effectively improve the immune function, 5‐year survival rate and local remission rate.